Application of Fractional-order Model Reference Adaptive Control on Industry Boiler Burning System - He, YaLi; Gong, RuiKun (2010 International Conference on Intelligent Computation Technology and Automation, 2010)
Fractional order model reference adaptive control was applied to control the temperature of boiler burning system, and simulation was made by Matlab/Simulink. The simulation result shows that it can still achieve good control effect even if control objects changed but control parameters not changed. It provides basis for using fractional order model reference adaptive control in the field of industry.